2011
DOI: 10.1074/jbc.m110.166132
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Collagen XVIII Long Isoforms Affects Kidney Podocytes, whereas the Short Form Is Needed in the Proximal Tubular Basement Membrane

Abstract: Collagen XVIII is characterized by three variant N termini, an interrupted collagenous domain, and a C-terminal antiangiogenic domain known as endostatin. We studied here the roles of this collagen type and its variant isoforms in the mouse kidney. Collagen XVIII appeared to be in a polarized orientation in the tubular basement membranes (BMs), the endostatin domain embedded in the BM, and the N terminus residing at the BMfibrillar matrix interface. In the case of the glomerular BM (GBM), collagen XVIII was ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 53 publications
3
42
0
1
Order By: Relevance
“…Kinnunen et al showed that although it is not noticeable in normal condition, the tubular BM of collagen XVIII deficient mice shows some structural abnormalities [16] which might result in an altered response after I/R and affect leukocyte influx and the degree of damage. However, that needs further research to be confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…Kinnunen et al showed that although it is not noticeable in normal condition, the tubular BM of collagen XVIII deficient mice shows some structural abnormalities [16] which might result in an altered response after I/R and affect leukocyte influx and the degree of damage. However, that needs further research to be confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, although additional studies are required to establish whether the COL18A1 c.331G > A variant itself (or an allele in linkage disequilibrium) is responsible for the triglyceride-lowering effect, from the data presented herein it seems conceivable that COL18A1 variants having a major deleterious impact on collagen XVIII's DUF/Fz sequences could cause atherogenic dyslipidemia and fatty liver, secondary to impaired adipogenesis. Furthermore, we note that factors regulating collagen XVIII expression may contribute to kidney health in later life by affecting the BM of proximal tubules (short isoform) and of glomerular podocyte foot processes (medium/long isoforms) (19). It may also be clinically relevant that short collagen XVIII is expressed widely in the BM of the retina, and that the retinal vessels of P1-, but not P2-mice develop the same vessel outgrowth abnormality seen in Col18a1 −/− mice (50).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, we measured the E of mouse and rat glomeruli using atomic force microscopy, micro-indentation, and microfluidics, and obtained values of 2–3 kPa [1416]. Although these studies measured isolated glomeruli that were not perfused, they detected physiologically meaningful alterations in glomerular elasticity because they demonstrated a reduced E with actin depolymerization (cytochalasin-D and latrunculin) and inhibition of non-muscle myosin II activity (blebbistatin) as well as in two disease states, Tg26 mice, a model of HIV nephropathy, and Col4a3 -/- mice, a model of Alport syndrome [15,16]. The reduced glomerular E in these models was surprising because the conventional view is that following injury, fibrosis develops progressively leading to a stiff, nonfunctional tissue.…”
Section: Introductionmentioning
confidence: 99%